Pengaruh Tingkat Intelegensi Dan Motivasi Belajar Terhadap Prestasi Belajar PAI Di MAN 1 Kota Sukabumi - Siti Nur Afifah; H. Mulyawan S. Nugraha (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
Education is basically a conscious effort to grow and develop the potential of human resources (HR), especially for students by providing encouragement and providing good facilities through learning activities. In addition, each individual must have the ability and willingness to learn so that the learning objectives can be achieved. The achievement of each individual from each learning process is called learning achievement. As for one of the supporting factors that are dominant in influencing learning achievement is the intelligence of each individual student. The purpose of this study is to find out how much influence the level of intelligence has on learning achievement, especially in the field of Islamic religious education (PAI) at MAN 1 Sukabumi City. The research method used is survey method with correlational analysis. Based on the results of the data analysis performed, it was found that intelligence has a significant effect on learning achievement. This is evidenced by the t count of 7.811 with a significance level of 0.01 and 0.05. Based on the data analysis test, it was also found that F was 61.011 with a significance value of 0.01 (p <0.05). This shows that intelligence has a significant influence on student achievement. Apart from the F value, an R square value of 0.592 is also obtained, which means that 59.2% of student achievement in PAI is influenced by the level of intelligence, while the remaining 40.8% is influenced by other factors such as motivation or learning environment. Then the results of the research conducted can be concluded that the level of intelligence has a significant effect on student achievement in PAI either partially or simultaneously. The other supporting factors are motivation, socioeconomic, class climate or learning methods which support student achievement, especially in Islamic Religious Education.